2018
DOI: 10.1249/jsr.0000000000000500
|View full text |Cite
|
Sign up to set email alerts
|

Physical Effects of Anabolic-androgenic Steroids in Healthy Exercising Adults: A Systematic Review and Meta-analysis

Abstract: Many athletes use anabolic-androgenic steroids (AAS) for physical enhancement but the magnitude of these gains and associated adverse effects has not been rigorously quantified. MEDLINE, EMBASE, Cochrane, SPORTDiscus, and PsycINFO were searched to identify randomized placebo-controlled trials of AAS in healthy exercising adults that reported one of the following outcomes: muscular strength, body composition, cardiovascular endurance, or power. Two authors appraised abstracts to identify studies for full-text r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 42 publications
0
22
1
Order By: Relevance
“…First, a general limitation of these studies results from the information about AAS doses and cycles of use/abuse, which is self-reported, and it is difficult to objectively assess the exact data. [84] Additionally, because of the stacking effect from polydrug abuse, it is difficult to assess the toxic effects of AAS. [85] These studies only demonstrated AAS-related cardiovascular lesions by observing the morphological and functional differences between the experimental group and the control group, which did not clarify the causality between AAS intake and disease development.…”
Section: Discussionmentioning
confidence: 99%
“…First, a general limitation of these studies results from the information about AAS doses and cycles of use/abuse, which is self-reported, and it is difficult to objectively assess the exact data. [84] Additionally, because of the stacking effect from polydrug abuse, it is difficult to assess the toxic effects of AAS. [85] These studies only demonstrated AAS-related cardiovascular lesions by observing the morphological and functional differences between the experimental group and the control group, which did not clarify the causality between AAS intake and disease development.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, testosterone, by binding to AR, produces an increased production of IGF-1, a decreased expression of myostatin and the differentiation of pluripotent mesenchymal cells into a myogenic lineage. These mechanisms are involved in an increase in protein synthesis, a decrease in protein breakdown, the formation of new myotubes as well as the increase in myonuclei number, thereby leading to the increase in muscle mass, strength and exercise capacity [94].…”
Section: Muscoloskeletal Systemmentioning
confidence: 99%
“…3,9 Adverse effects: The most common adverse effects include abnormalities in lipid profile (decreased high density lipoproteins and increased low density lipoprotein) and hepatic enzymes (increased aspartate aminotransferase); and mood disturbances (irritability, psychotic symptoms and depression). 10 The serious adverse effects include infertility in males, masculinisation in females, cardiovascular risks, tumours of liver and kidney and premature skeletal maturation. 3 Other less common ones include acne, alopecia, injection site reactions, increased haematocrit and decreased testicular size.…”
Section: Anabolic Agentsmentioning
confidence: 99%
“…3 Other less common ones include acne, alopecia, injection site reactions, increased haematocrit and decreased testicular size. 10…”
Section: Anabolic Agentsmentioning
confidence: 99%